2000
DOI: 10.1155/2000/570265
|View full text |Cite
|
Sign up to set email alerts
|

Chemical structures of macrocyclic bis(bibenzyls) isolated from liverworts (Hepaticae)

Abstract: Liverworts (Hepaticae) produce a number of macrocyclic bis(bibenzyls) which show interesting biological activity and are of very valuable for the chemosystematic study of liverworts. The structural elucidation of these characteristic natural products are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 29 publications
0
80
0
Order By: Relevance
“…10 Studies and clinical trials have demonstrated that marchantin C has antibacterial, antifungal, and antioxidant properties, 6,7 as well as suppression of the growth of several cancer cells, such as A172, K562 and HepG2. 9 In the present study, we focused our main scope on the anti-invasiveness and anti-angiogenic activity Recovery of each denuded area was quantified by densitometric analyses relative to that of the control which was set at 100% as shown in the graph.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Studies and clinical trials have demonstrated that marchantin C has antibacterial, antifungal, and antioxidant properties, 6,7 as well as suppression of the growth of several cancer cells, such as A172, K562 and HepG2. 9 In the present study, we focused our main scope on the anti-invasiveness and anti-angiogenic activity Recovery of each denuded area was quantified by densitometric analyses relative to that of the control which was set at 100% as shown in the graph.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated to exhibit multiple pharmacological activities such as antimicrobial activity against the Grampositive bacterium Bacillus subtilis, 6 antioxidant activity to free radicals, 5 and anti-tumor activity against A172 glioma cells. 8 Recently, we found that marchantin C abrogated microtubule dynamics and mitotic spindle formation, resulting in cell cycle arrest at G 2 /M phase and eventually leading to cell death both in vitro and in vivo.…”
Section: Marchantin C a Potential Anti-invasion Agent In Glioma Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial activity of flavonoids has been reported (Singh & Bhat, 2003). Asakawa (1990Asakawa ( , 2001 and Asakawa et al (2000) stated that almost all species of bryophytes are not damaged by insect larvae, fungi, bacteria, slugs, snails and mammals because, biological compounds like oligosaccharides, polysaccharides, sugar alcohols, amino acids, fatty acids, aliphatic compounds, phenyl quinone and aromatic phenolic substances in bryophytes are protected against these organisms. It is well known that plant phenols, particularly the free phenols (whichare toxic substances) play a significant role in controlling pathogenic microorganisms attacking some variety of plants.…”
Section: Introductionmentioning
confidence: 99%
“…Bisbibenzyls, a class of plant metabolites produced exclusively in liverworts, is a family of phenolic compounds belonging to stilbenoids (9). They have attracted more attention for their wide-range of bioactivity and medicinal potency, including antibacterial, antifungic, antioxidative, muscle-relaxing and cytotoxic activities as well as inhibitory effects on 5-lipoxygenase, cyclooxygenase and calmodulin (10).…”
Section: Introductionmentioning
confidence: 99%